Relações culturais e comunicativas no processo de criação do compositor Gilberto Mendes - Zago, Rosemara Staub de Barros (2002)
The objective of this research is to understand the process of creation of Gilberto Mendes (1922 -) composer, based on the analysis of materials that he used during the construction of his musical work. Among the analysed papers, we should emphasize his notebook, letters and his work project. To understand the complexity of information that we found in the registers, we follow as theoric framework, the Semiotic by Charles Sanders Peirce, that discusses the sign action process, and the Genetic Criticism, as the main tooll for the description, interpretation and analyses of the process papers. Divided in three chapters, we show in the first one the cultural aspect that "guided" the artist life, Genetic Criticism as a theoric tooll to analyse the "process papers", and the description from what we found in these documents. In the second chapter, we discuss about the "tendency" and purpose that follows the construction of the composer's poetic project, his cultural and communicative relation between his musical work and his cultural background, envolving the music, the american cinema, in the first half of the 20 th century, and the modern visual arts. Finally, in the third chapter, we analyse the verbal, visual and cinematographic language as means of intersemiotic translation, used by the composer during the creation development of his musical work. To summarize, we got to the end of the work knowing a little more about the mechanism process of his artistic creation and his communicative and cultural relation